Evaluation of the measurement properties of symptom measurement instruments for atopic eczema: a systematic review. Issue 1 (13th July 2016) - Gerbens, L. A. A.; Prinsen, C. A. C.; Chalmers, J. R.; Drucker, A. M.; von Kobyletzki, L. B.; Limpens, J.; Nankervis, H.; Svensson, Å.; Terwee, C. B.; Zhang, J.; Apfelbacher, C. J.; Spuls, P. I.; et al.
Abstract: Background: Symptoms have been identified as a core outcome domain for atopic eczema (AE) trials. Various instruments exist to measure symptoms in AE, but they vary in quality and there is a lack of standardization between clinical trials. Our objective was to systematically evaluate the quality of the evidence on the measurement properties of AE symptom instruments, thereby informing consensus discussions within the Harmonising Outcome Measures for Eczema (HOME) initiative regarding the most appropriate instruments for the core outcome domain symptoms. Methods: Using the COnsensus‐based Standards for the selection of health Measurement INstruments (COSMIN) checklist and predefined criteria for good measurement properties on identified development and validation studies of AE symptom instruments, a best evidence synthesis was performed to draw an overall conclusion on quality of the instruments and to provide recommendations. Results: Eighteen instruments were identified and evaluated. When the quality and results of the studies were considered, only five of these instruments had sufficient validation data to consider them for the core outcome set for the core outcome domain symptoms. These were the paediatric Itch Severity Scale (ISS), Patient‐Oriented Eczema Measure (POEM), Patient‐Oriented SCOring Atopic Dermatitis (PO‐SCORAD), Self‐Administered Eczema Area and Severity Index (SA‐EASI) and adapted SA‐EASI. Conclusions: ISS (paediatric version), POEM, PO‐SCORAD, SA‐EASI and adapted SA‐EASI are currently the most appropriate instruments and therefore have the potential to be recommended as core symptom instrument in future clinical trials. These findings will be utilized for the development of a core outcome set for AE.